Surviving the Applewhites - Tolan, Stephanie S. (New York Scholastic, 2003)
Jake, a budding juvenile delinquent, is sent for home schooling to the arty and eccentric Applewhite family's Creative Academy, where he discovers talents and interests he never knew he had.
Newbery Honor book for 2003.
86066
Keywords: Eccentrics and eccentricities -- Fiction; Theater -- Fiction; Family -- North Carolina -- Fiction; North Carolina -- Fiction